1974
DOI: 10.1111/j.1365-2028.1974.tb01038.x
|View full text |Cite
|
Sign up to set email alerts
|

The natural regulation of buffalo populations in East Africa: The food supply as a regulating factor, and competition*

Abstract: Summary Evidence is presented to show that both the quality and quantity of food available to a buffalo population falls below the minimum maintenance requirements of that population at certain times of the year. In the Serengeti grasslands there was a shortage of the only good quality component, grass leaf, in the dry season, with the result that the animals consumed an increasing proportion of poor quality food such as grass stem. By the end of the dry season the diet had dropped in quality below the minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(19 citation statements)
references
References 30 publications
2
16
1
Order By: Relevance
“…The effects of drought are most strongly felt when animal populations experience extreme food limitation and either engage in limited movements or occupy habitats that experience droughtrelated food limitation at some stage on their migration -like the Mara-Serengeti wildebeest. Our finding that the Mara-Serengeti buffalo population is limited by food supply not only supports the food limitation hypothesis (H 1 ) but is also supported by several previous studies in the region (Sinclair 1973b(Sinclair , 1974b(Sinclair , 1977(Sinclair , 1983(Sinclair , 1985Dublin et al 1990a). Indeed, following his long-term study on the African buffalo in the Serengeti, Sinclair (1977), argued that the importance of food limitation to buffalo has led to the evolution of specific behavioural strategies and physiological mechanisms to detect and avoid food shortages.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The effects of drought are most strongly felt when animal populations experience extreme food limitation and either engage in limited movements or occupy habitats that experience droughtrelated food limitation at some stage on their migration -like the Mara-Serengeti wildebeest. Our finding that the Mara-Serengeti buffalo population is limited by food supply not only supports the food limitation hypothesis (H 1 ) but is also supported by several previous studies in the region (Sinclair 1973b(Sinclair , 1974b(Sinclair , 1977(Sinclair , 1983(Sinclair , 1985Dublin et al 1990a). Indeed, following his long-term study on the African buffalo in the Serengeti, Sinclair (1977), argued that the importance of food limitation to buffalo has led to the evolution of specific behavioural strategies and physiological mechanisms to detect and avoid food shortages.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, the conclusion that competition alone was of overriding importance in the regulation of the buffalo (Sinclair 1974b(Sinclair , 1977Dublin et al 1990a) seems insufficient to explain dramatic changes in the buffalo population in the Mara-Serengeti between 1984 and 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In the Serengeti ecosystem long-term studies on buffalo (Sinclair 1974(Sinclair , 1977 and wildebeest demonstrated that predation did not have a major impact on these populations which were mainly regulated by food supply, especially during dry years.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the buffalo had the lowest value for colonic water absorption of all species investigated. Accordingly, African buffalo depend on the availability of drinking water (Sinclair 1974;Field 1976). Bartocci et al (1997), Clauss et al (1998) and Behrend (2000).…”
Section: Limitations To Forestomach Capacity Increasementioning
confidence: 99%